2021
DOI: 10.3390/microorganisms9122411
|View full text |Cite
|
Sign up to set email alerts
|

Metataxonomic Analysis of Bacteria Entrapped in a Stalactite’s Core and Their Possible Environmental Origins

Abstract: Much is known about microbes originally identified in caves, but little is known about the entrapment of microbes (bacteria) in stalactites and their possible environmental origins. This study presents data regarding the significant environmental distribution of prokaryotic bacterial taxa of a Greek stalactite core. We investigated the involvement of those bacteria communities in stalactites using a metataxonomic analysis approach of partial 16S rRNA genes. The metataxonomic analysis of stalactite core materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 65 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…Cave microbial communities are affected by rock types and surface-soil richness/poorness, resulting in various geochemical and hydrochemical features of cave streams, such as pH, organic/inorganic nutrient availability, and buffering action [ 6 , 7 ]. On the other hand, cave microbial communities are likely involved in the formation of various geological forms, such as stalactites in limestone caves [ 8 ] and “champignons”, i.e., mushroom-like white speleothems, uniquely found in silicate caves [ 9 ]. The roles of microorganisms have been well studied but perhaps are still poorly understood [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cave microbial communities are affected by rock types and surface-soil richness/poorness, resulting in various geochemical and hydrochemical features of cave streams, such as pH, organic/inorganic nutrient availability, and buffering action [ 6 , 7 ]. On the other hand, cave microbial communities are likely involved in the formation of various geological forms, such as stalactites in limestone caves [ 8 ] and “champignons”, i.e., mushroom-like white speleothems, uniquely found in silicate caves [ 9 ]. The roles of microorganisms have been well studied but perhaps are still poorly understood [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…They contain small volumes of water trapped within and between the calcite crystals of commonly named liquid inclusions, like the bubbles in ice cores. Rainwater from the cave surrounding area penetrates the ground and epicarst; consequently, it is carried through microcracks and eventually drips from the soda straws suspended from the roof of the cave down on the stalagmites ( Michail et al 2021 ). Based on the above, it is difficult to find instant, unchanged water, dispersed by previous rainfall on land and in caves around the world, able to construct stalactites and stalagmites that incorporate fossil water and trap well-preserved bacteria over millennia, a natural environment ( Affolter et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent data have shown that cave sediments, as oligotrophic environments, host a highly heterogeneous phylogenetic pluralism dominated by Actinomycetota and Proteobacteria. The prevalence of Proteobacteria species in the stalactite core structure may be related to their fast development rates in rich nutrient habitats (uppermost ground cave surroundings), establishing a substitute for the ground carbon input ( Michail et al 2021 ). De Mandal et al (2017) proposed that bacteria correspond to a significant part of a cave’s ecosystem and play an essential role in preserving a cave’s biodiversity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations